TRAILERY GIER WIDEO. ANALIZA CECH FORMALNYCH I GATUNKOWYCH - Sikorska , Joanna (Studia Europaea Gnesnensia, 2018)
The paper aims to outline the formal and genre features of video game trailers, analyzing those using animation and gameplay scenes, as well as material combining both elements. The author focuses on cinematic devices in such trailers and discusses the differences between video game trailers and trailers promoting movie productions.